Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.6025/jdim/2020/18/1/21-32
|View full text |Cite
|
Sign up to set email alerts
|

Rumor Retransmission on Twitter: Message Characteristics, user Characteristics and Retransmission Outcomes

Abstract: This paper seeks to depict online rumor retransmission using three main constructs, namely, message characteristics, user characteristics and retransmission outcomes. In particular, it teases retransmission outcomes into volume, immediacy and lifespan of rumor tweets. The dataset was drawn from 322 original Twitter messages which generated some 5,700 retweets about the rumored death of Lee Kuan Yew (LKY). Content analysis and statistical tests were conducted. The results confirm the robustness of the research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…They find positive emotions perceived appropriateness was highest for WhatsApp as compared to other social media channels (Waterloo et al, 2018). Based on prior literature, the current research posits, the polarity of a message affects its retransmission (Chua and Chen, 2020) such that positive messages will be shared more than negative messages on social media. The following is hypothesised:…”
Section: Effect Of Message Polarity On Sharing and Verifying Behaviour On Social Mediamentioning
confidence: 88%
See 3 more Smart Citations
“…They find positive emotions perceived appropriateness was highest for WhatsApp as compared to other social media channels (Waterloo et al, 2018). Based on prior literature, the current research posits, the polarity of a message affects its retransmission (Chua and Chen, 2020) such that positive messages will be shared more than negative messages on social media. The following is hypothesised:…”
Section: Effect Of Message Polarity On Sharing and Verifying Behaviour On Social Mediamentioning
confidence: 88%
“…Message polarity invokes emotions that could be positive or negative depending on whether the consequence of the message is positive or negative (Kamins et al, 1997;Chua and Chen, 2020).…”
Section: Effect Of Message Polarity On Sharing and Verifying Behaviou...mentioning
confidence: 99%
See 2 more Smart Citations
“…Another theme of research took a hybrid perspective to combine the information evaluation as well as beliefs and emotions in characterizing the rumor-sharing behavior. They found that the message or information factors, belief, and emotional factors (e.g., perceived severity and perceived fear) worked synthetically in shaping the intention to share rumors ( Chua and Chen, 2020 ; Laato et al., 2020 ). However, during the crisis, rumor sharing was found not affected by human authenticating behavior due to the time limitation ( Talwar et al., 2020 ), which indicated that people might not have time or did not want to spend time evaluating the rumor systematically in that context.…”
Section: Discussionmentioning
confidence: 99%